When great responsibility comes with limited options: experiences and needs of older community-dwelling adults regarding accessing, understanding, appraising and using health-related information - Sonja Stelly Gustafsdottir; Lena Mårtensson; Arun K. Sigurdardottir; Solveig A. Arnadottir (BMC Geriatrics, 2024)
Abstract Background In previous research, older adults have been associated with reduced levels of health literacy (HL) influenced by a range of contextual factors. To optimise HL, it is essential to better understand the interactions between the ageing process and both personal and environmental factors as perceived by older adults. This study aimed to explore the experiences and needs of older community-dwelling adults when accessing, understanding, appraising and using health-related information. Methods An explorative, qualitative design was used within the social constructivism framework. Semi-structured individual interviews were conducted with 20 adults aged 70–96 living at home in three areas in Northern Iceland. The transcribed interviews were constructed into categories and subcategories using qualitative content analysis. Findings. Four categories emerged. “Expectations for responsibility” describes the experience that individuals are responsible for taking care of their health, including accessing, understanding, appraising and using information and services, showing initiative and keeping needed communications active. “A gap between expectancy and ability/context” includes experiences while taking responsibility for expectations not aligning with skills/situations, creating information gaps. “Finding one’s own ways” comprises various adapted ways to access, understand, and use information and services. “Bridging the gap” describes experiences of needing shared responsibility and more manageable options to enable reasoned health-related decisions and navigation in the healthcare system. Conclusions The participants valued and took full responsibility for accessing, understanding, appraising and using information and services as part of a social norm; however, they experience information gaps. They request shared responsibility by being provided with fundamental health-related information as a vital step in making reasoned health-related decisions and navigating the healthcare system. They also ...